Eksperimentasi Penciptaan Karya Keramik Monumental Dengan Tungku Rekayasa - Marwanto, Aries Budi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
In the process of creating ceramic art, the size scale is a problem. When making large ceramic works, meaning the risk of failure too great. This relates well with the chemical composition of clay and the right mixture. After the drying process is also longer, but the longer the drying period is the longer the duration of the crack or rupture prone. Last is a burning issue that must use a big oven. Larger furnace is also more expensive. Some of these cons-traints which ultimately makes ceramic artists in Indonesia did not dare to experiment making great work. Complex process coupled with the limitations of the furnace equipment (oven) for high-priced, making leaps of the idea of creation of ceramic artists and Indonesia not seprogresif dyna-mic branch other art. Es-pecially in terms of its magnitude. Noted, functional ceramics produced most only 2 meters, which is in Plered West Java, while the ceramic art ever created by Dadang Chris-tanto very monu-mental in his "1000 man land". The fact is captured by the author. Article "Creation Experi-mentation Stove Works Engi-neering Ceramics Using" this merrupakan exploration of the possibility of aspects of the main raw material composition (clay structure and all materials mixed), initial combustion process, and the main thing is burning stove model development, which is inspired from the stove burning bricks. Keywords: Experimentation, Cera-mics, Sculptures Monumental, Furnace Combustion Engineering.